Understanding Dynamics of Initial Trust and its Antecedents in Password Managers Adoption Intention among Young Adults - Farooq Ali; Dubinina Alina; Virtanen Seppo; Isoaho Jouni (Netherlands, 2022)
Security professionals often suggest password managers as one of the best measures for the end-users. However, the end-users have shown reluctance in adopting them, mostly due to the trust factor. The purpose of the paper was to examine the relationship of initial trust, and it's antecedents with the password manager's adoption intention. In this regard, using the Initial Trust Model as a framework, data from 289 respondents (age 18-35) were collected through a crowdsourcing website and analyzed using structural equation modeling (SEM) in SmartPLS 3.2. Results show that initial trust has a significant effect on the intention to adopt a password manager. In initial trust formation, firm reputation and structural assurances play a significant role, whereas personal propensity to trust does not significantly relate to initial trust. Moreover, firm reputation and structural assurances indirectly affect intention to adopt password managers
The 12th International Conference on Ambient Systems, Networks and Technologies (ANT) / The 4th International Conference on Emerging Data and Industry 4.0 (EDI40) / Affiliated Workshops